Altruism, fast and slow? Evidence from a meta-analysis and a new experiment - Hanna Fromell; Daniele Nosenzo; Trudy Owens (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2018)
Can we use the lens of dual-system theories to explain altruistic behavior? In recent years this question has attracted the interest of both economists and psychologists. We contribute to this emerging literature, by reporting both the results of a meta-study of the literature and a new experiment. Our meta-study is based on 19 experimental studies conducted with nearly 11,000 subjects. We show that the overall effect of manipulating cognitive resources to promote the "intuitive" system at the expense of the "deliberative" system is very close to zero. We argue that this null result could be because the interventions used in the existing literature to manipulate cognitive resources are vulnerable to the presence of heterogeneity in the direction of the effect of the intervention. We design a new experiment that is not vulnerable to this potential heterogeneity. We still fail to find support for the notion that altruistic choices are the result of a conflict between the intuitive and deliberative systems. Taken together, the findings of our meta-study and the new experiment offer little support for dual-system theories of altruistic behavior.
Keywords: C91; 330; altruism; giving; dictator game; dual-system model; intuition; deliberation; selfcontrol; willpower; depletion; Stroop task